Effects of granule particle size and lubricant concentration on tablet hardness containing large concentration of polymers - Chauhan Rajani; Dewangan Devendra Kumar; Dwivedi Jaya; Jha Arvind Kumar (Brazilian Journal of Pharmaceutical Sciences, 2018)
ABSTRACT The objective of this research work is to demonstrate the impact of granule size and lubricant concentration on the hardness of tablets in formulations containing higher concentration of polymers and to resolve the hardness issue during compression process. The work involves optimization of a milling process for size reduction of granules and blending process to achieve tablets of good hardness on compression. To optimize the granule size, different sized co-mill screens were used. The different concentration of lubricant were studied on different sized granules to check the effect on hardness of tablets and to obtained the desired hardness of tablets. Compression of lubricated blend in various concentration was performed using the gravity feeder and force feeder separately to check the impact on the over lubrication effect. This ultimately leads to less hardness tablets. Lubricated blends were evaluated by performing the Bulk Density, Tapped Density, Hausner ratio and compressibility index tests. Tablets were evaluated for the physical characteristics like weight variation, hardness, thickness and dissolution. It has been conclude that on using the optimum granules size and lubricant concentration in formulation, all the downstream problems can be resolved and this in turn helps in compression of tablets and also provides the good hardness to the tablets.